2020
DOI: 10.1093/her/cyaa028
|View full text |Cite
|
Sign up to set email alerts
|

‘I will welcome this one 101%, I will so embrace it’: a qualitative exploration of the feasibility and acceptability of HIV self-testing among men who have sex with men (MSM) in Lagos, Nigeria

Abstract: Men who have sex with men (MSM) are disproportionately affected by HIV in Nigeria. A key strategy in reducing transmission is to increase HIV testing uptake and linkage to treatment for those who test positive. HIV self-testing (HIVST) is an innovative strategy with the potential to increase uptake of HIV testing among key populations at higher risk for HIV. We conducted 23 in-depth-interviews with MSM and two focus group discussions with key opinion leaders to explore perceptions about the feasibility and acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 24 publications
2
14
0
7
Order By: Relevance
“…Selecting the appropriate mode of kit distribution was important to ensure accessibility and adoption [57,78,90,92,99,104,105,108,110,112,119,122,137,139,141,163,184,189,190,202,204]. Modes of distribution described include: (1) direct delivery by community health workers, peers, partners, and sex workers, (2) Home delivery, and (3) Pick up at health facilities or community-based organizations or other sites (e.g., health clubs, markets, private pharmacies, vending machines).…”
Section: Positive Perceptions On Hiv-stmentioning
confidence: 99%
See 2 more Smart Citations
“…Selecting the appropriate mode of kit distribution was important to ensure accessibility and adoption [57,78,90,92,99,104,105,108,110,112,119,122,137,139,141,163,184,189,190,202,204]. Modes of distribution described include: (1) direct delivery by community health workers, peers, partners, and sex workers, (2) Home delivery, and (3) Pick up at health facilities or community-based organizations or other sites (e.g., health clubs, markets, private pharmacies, vending machines).…”
Section: Positive Perceptions On Hiv-stmentioning
confidence: 99%
“…Other reported considerations when designing HIV-ST programs included (1) adequate follow-up [100,113,118,120,127,135], (2) establishment of peer support networks [78, 104,107,122,140,199] and, (3) proper education on HIV-ST use [93, 98-100, 102, 106, 108-110, 112, 116, 120, 122, 127, 131, 133, 139, 140, 190, 196, 201, 206]. Education, both at the individual and community level, ensures proper technique and addresses any concerns on test accuracy.…”
Section: Positive Perceptions On Hiv-stmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the study and its main ndings can be found elsewhere. [21,22] In this study, focus group discussions with the KOLs who distributed the HIVST kits and semi-structured in-depth interviews (IDIs) with MSM who received the kits were conducted three months after the kits were distributed.…”
Section: Methods Study Designmentioning
confidence: 99%
“…This project was the rst implementation science research project to examine a distribution modality for HIVST kits among MSM in Nigeria. [22] In this paper, we describe the operationalization of this strategy based on qualitative interviews with KOLs and MSM who participated in this study.…”
Section: Introductionmentioning
confidence: 99%